Human Capital Investment and the Gender Division of Labor in a Brawn-Based Economy - Pitt, Mark M; Rosenzweig, Mark R; Hassan, Mohammad Nazmul (American Economic Review, 2012)
We use a model of human capital investment and activity choice to explain facts describing gender differentials in the levels and returns to human capital investments. These include the higher return to and level of schooling, the small effect of healthiness on wages, and the large effect of healthiness on schooling for females relative to males. The model incorporates gender differences in the level and responsiveness of brawn to nutrition in a Roy-economy setting in which activities reward skill and brawn differentially. Empirical evidence from rural Bangladesh provides support for the model and the importance of the distribution of brawn.